Quantitative interpretation of impedance spectroscopy data on porous LSM electrodes using X-ray computed tomography and Bayesian model-based analysis. Issue 37 (11th September 2017) - Brunello, Giuseppe F.; Epting, William K.; de Silva, Juwana; Salvador, Paul A.; Litster, Shawn; Finklea, Harry O.; Lee, Yueh-Lin; Gerdes, Kirk R.; Mebane, David S.
Abstract : With Bayesian calibration the uncertainty of the temperature dependence of the TPR current can be obtained. Abstract : It is broadly understood that strontium-doped lanthanum manganate (LSM) cathodes for solid oxide fuel cells (SOFCs) have two pathways for the reduction of oxygen: a surface-mediated pathway culminating in oxygen incorporation into the electrolyte at the triple-phase boundary (TPB), and a bulk-mediated pathway involving oxygen transfer across the electrode–electrolyte interface. Patterned electrode and thin film experiments have shown that both pathways are active in LSM. Porous electrode geometries more commonly found in SOFCs have not been amenable for precise measurement of active electrode width because of the difficulty in precisely measuring the electrode geometry. This study quantitatively compares a reaction–diffusion model for the oxygen reduction reaction in LSM to the impedance spectrum of an experimental LSM porous electrode symmetric button cell on a yttria-stabilized zirconia (YSZ) electrolyte. The porous microstructure was characterized using computed tomography (nano-CT) and Bayesian model-based analysis (BMA) was used to estimate model parameters. BMA produced good fits to the data, with higher than expected values for the interfacial capacitance at the LSM–YSZ interface and vacancy diffusion activation energy; these results may indicate that the active width of the electrode is on a similar scale with that of the space-charge width at the LSM–YSZ interface. The analysis also showed that the active width and proportion of current moving through the bulk pathway is temperature dependent, in accordance with patterned electrode results.